PEMANFAATAN MEDIA SOSIAL INSTAGRAM PADA AKUN @SENDI_DPP SEBAGAI MEDIA KOMUNIKASI DIGITAL PERTANIAN CERDAS - Afifah Nur Khasanah; Lestarini, Niken (Jurnal Ilmu Komunikasi, 2026)
This study examines the utilization of Instagram as a digital communication medium for AI-based smart agriculture through a case study of the @sendi_dpp account. Employing a descriptive qualitative method, the research analyzes communication strategies, content characteristics, and audience responses through in-depth interviews with the account manager and some active followers, as well as digital observation of published content. Findings reveal that Instagram effectively educates the public about smart agriculture through short-duration reels format, simplification of technical information using conversational language, demonstrative visualization, and responsive two-way interaction. The study identifies significant perceptual transformation among audiences, particularly young generation, from viewing agriculture as a traditional sector to recognizing it as modern and prospective. Content successfully enhances digital agricultural literacy, encourages organic sharing behavior, and motivates active knowledge seeking. Instagram proves to provide a conducive ecosystem for visual educational communication with significant reach, engagement, and impact in transforming negative stigma about agriculture and attracting young generation's interest toward agritech innovation in Indonesia. Keywords: Artificial Intelligence, Digital Communication, Instagram, Smart Agriculture, Young Generation